Analysis of consumers’ preference and willingness to pay for orange-fleshed sweet potato in Osun state, Nigeria (International Journal of Agricultural Research, Innovation and Technology, 2024)
This study assesses the factors that influence consumers’ preference and willingness to pay (WTP) for orange-fleshed sweet potato (OFSP), emphasizing the effects of information on its health benefits. A multi-stage sampling technique was employed to select 180 respondents for study. Primary data were collected using a well-structured and pre-tested questionnaire. Data were subjected to descriptive and inferential statistics, viz, the hedonic pricing and probit models.  The results show that factors such as gender, root size, availability and storability influence consumers’ preference for OFSP. The results further revealed that the root size negatively influenced preference for OFSP, while availability positively influenced it. These results also indicate that preference for OFSP decreases with the length of storage. In terms of willingness to pay for OFSP, the result of the hedonic pricing model indicates that the age of the respondent and colours of the OFSP positively influence consumers’ willingness to pay for OFSP.  There was a (17.1%) increase in consumers’ level of preference after information on the health benefit was provided to them and the result from comparing means (T-Test) of prices consumers are willing to pay before and after information was provided showed a negative co-efficient (-16.341), which was significant at 1% level of significance. We suggest that research should concentrate on identified OFSP characteristics to improve acceptance, while in the short run, there is a need to promote OFSP production to increase availability.Int. J. Agril. Res. Innov. Tech. 14(1): 53-61, June 2024